Traditional Games for Strengthening Sportsmanship and Cooperation in Elementary School Physical Education - Mochamad Rizki Firdaus; Tedi Supriyadi; Aam Ali Rahman (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study investigates the role of traditional games in strengthening sportsmanship and cooperative behavior in elementary school physical education. Using a qualitative case study approach, the research involved one physical education teacher and 20 fifth-grade students. Data were collected through observations, interviews, and documentation, then analyzed using thematic analysis. The novelty of this study lies in its focus on how social values are naturally developed through students’ interactions during game-based learning activities. The findings reveal that students developed fair play attitudes, rule compliance, emotional control, communication skills, responsibility, and collaborative problem-solving abilities during learning activities. However, several challenges were still identified, including passive participation and inconsistent social behavior among some students. The findings indicate that sportsmanship and cooperation develop simultaneously through social interaction during traditional games. Therefore, traditional games can serve as an effective and contextual approach for fostering students’ social and emotional development in physical education.